Редукція складності моделей мережевих структур та систем - Поліщук, О.Д. (Доповіді НАН України, 2019)
Аналізується проблема складності мережевих структур та систем. Визначаються кількісні показники
складності мережі та їх застосування для вибору ефективної моделі структури системи. Пропонуються методи редукції складності моделей мережевих систем з одночасним відстеженням збереження міри їх адекватності. Ефективність запропонованих підходів ілюструється на прикладах реальних складних систем. Анализируется проблема сложности сетевых структур и систем. Определяются количественные показатели сложности сети и их использование для выбора эффективной модели структуры системы. Предлагаются методы редукции сложности моделей систем с одновременным отслеживанием сохранения меры их адекватности. Эффективность предложенных подходов иллюстрируется на примерах реальных
сложных систем. The problem of complexity of network structures and systems is analyzed. The quantitative indicators of the
dimensional and connective network complexity are determined, and examples of their application for choosing
an effective model of the system structure are given. The methods of reduction of the complexity of models of
network systems are offered, taking into account that such systems can be investigated only in general. The first
of these approaches consists in the identification and exclusion of fictitious elements from the network, i.e. nodes
and edges are formally included in the structure, but not involved in the system operation. This allows us to reduce
the complexity of many real system models by dozens. The concepts of flow adjacency matrix and the flow
core of a network system determining the most functionally important components of it are introduced. In the
simplest case, the flow cores allow us to exclude the transit nodes from the system model, i.e. elements which do
not add or remove the part of flows that are moving through the network. The specific weight of the flow core
determines how adequate is its model in comparison with the source network model. A number of examples show
that the flow cores significantly reduce the complexity of system models. The method of encapsulation of the
components of supplements to flow cores is proposed to increase the adequacy of their models. The main features
of subnets that can be encapsulated are determined, and examples of real systems are given, for which the encapsulation
method reduces the dimension of their models by dozens and more without significant loss of adequacy.